COMPARISON OF GROWTH OF MANGROVE TYPES OF RHIZOPHORA SPP USING POLYBAG AND HYDROPONIC MEDIA IN KARIMUNJAWA NATIONAL PARK, CENTRAL JAVA - Pasaribu, Roberto Patar; Djari, Anthon Anthonny; Rahman, Abdul; -, Aris Kabul (Jurnal Segara, 2024)
Mangroves are one of the ecosystems that grow in places that are influenced by the around the coast and river mouths. The technique of planting and maintaining mangrove seedlings varies from place to place depending on the media and conditions in the field. The purpose of this study was to compare the growth of mangrove species Rhizophora spp on two different nursery media, namely polybag and hydroponic media. This research was conducted in Karimunjawa National Park, Central Java, with an experimental research method. The results showed the growth rate of mangrove seedlings using polybag media was an average of 0.64cm per fortnight, while with hydroponic media it was 0.44cm per fortnight. The first leaf growth with polybag media occurred in the fifth week after planting while for hydroponic media the leaves grew in the sixth week. The survival rate on polybag media is 92.31%, while in hydroponic media it is 84.61%